2020
DOI: 10.3897/phytokeys.144.33287
|View full text |Cite
|
Sign up to set email alerts
|

Onosma fuyunensis (Boraginaceae), a new species from Xinjiang, China

Abstract: Onosma fuyunensis, a new species of Boraginaceae from northern Xinjiang, China, is described and illustrated here. Onosma fuyunensis is similar to O. simplicissima and O. gmelinii; it differs in having a particularly bristly indumentum, unbranched stems, white and yellow corollas, anthers united only at base, and nutlets with a stipitate cicatrix. An updated key to the species of Onosma from Xinjiang and Altai Mountains is also provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Many species of the genus Onosma have been reported as medicinal plants that contain rich bioactive compounds (Pandey 1970 ; Gu 2016 ; Sher et al 2016 ). O. fuyunensis is a newly reported species distributed in Xinjiang, China (He et al 2020 ). In this study, we sequenced the complete chloroplast genome of O. fuyunensis , provided the first chloroplast genome in this genus and tribe Lithospermeae.…”
mentioning
confidence: 99%
“…Many species of the genus Onosma have been reported as medicinal plants that contain rich bioactive compounds (Pandey 1970 ; Gu 2016 ; Sher et al 2016 ). O. fuyunensis is a newly reported species distributed in Xinjiang, China (He et al 2020 ). In this study, we sequenced the complete chloroplast genome of O. fuyunensis , provided the first chloroplast genome in this genus and tribe Lithospermeae.…”
mentioning
confidence: 99%
“…The new taxa were assessed based on the diagnostic keys of Flora Iranica (Riedl, 1967), Flora of Iran (Khatamsaz, 2002), Flora of Turkey (Riedl, 1979), Flora of USSR (Popov, 1953), Boissier (1879), Johnston (1954), Post (1966), Polunin (1969), Ball (1972) and Nasir & Ali (1979). Several newly introduced taxa of Onosma were evaluated and compared with our new taxa (see: Teppner, 1980; Ghahreman and Attar, 1996; Attar and Joharchi, 2006; Attar and Hamzehee, 2007; Binzet and Orcan, 2007; Kandemir and Türkemen, 2010; Aytac and Türkmen, 2011; Koyuncu et al, 2013; Mehrabian et al, 2013; Ahmad, 2014; Binzet, 2016 a, b; Cecchi et al, 2016; Binzet and Eren, 2018; Mehrabian and Amini Rad, 2018; Mehrabian and Mozaffarian, 2018; Dehshiri, 2018; He et al, 2018, 2020). Additionally, more than 2500 accessions of Onosma specimens, and images of type specimens in several herbaria of Iran (HSBU!, TARI!, IRAN!)…”
Section: Methodsmentioning
confidence: 99%
“…Onosma L. (Boraginaceae tribe Lithospermeae ) is an Old‐World genus of biennial to perennial herbs, comprising about 240 species (He et al, 2020) mainly distributed in xeric habitats with rocky to sandy soils and serpentine geological outcrops (Mengoni et al, 2006; Cecchi et al, 2011). Its distribution ranges between Morocco in the west and the Pan‐Himalaya region in the east, with the main center of diversity in the Irano‐Turanian region (Meusel et al, 1978; Takhtajan, 1986; Mehrabian et al, 2013; Cecchi et al, 2016; Weigend et al, 2016; He et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, no consensus was reached on the nature of the Junggar terrane basement. For example, one model suggested that the Junggar terrane has a Precambrian basement (Xiao et al, 1992;He et al, 1994;Ma et al, 1997;Li, 2004;Charvet et al, 2007;Bazhenov et al, 2003Bazhenov et al, , 2012Zhang et al, 2013;Xu et al, 2015), but another model envisaged a basement of Paleozoic oceanic crust (Jiang, 1984;Hsü, 1988;Li, 1989;Carroll et al, 1990;Dobretsov et al, 1995;Windley et al, 2007), and a third model proposed a suprasubduction, oceanicisland-arc basement (Coleman, 1989;Chen and Jahn, 2004;Şengör et al, 1993;Jahn et al, 2000;Şengör and Natal'in, 1996;Xiao et al, 2004Xiao et al, , 2006Xiao et al, , 2008aXiao et al, , 2008bXiao et al, , 2009Xiao et al, , 2010Xiao et al, , 2013Xiao et al, , 2015. In parallel with this controversy, the nature of the Dananhu-Haerlik arc has been debated for several decades.…”
Section: Nature Of the Dananhu-haerlik Arcmentioning
confidence: 99%